Analysis of single fly ash particles using laser ablation ICP-MS – an approach achieving lateral elemental distribution information via imaging. Issue 33 (10th April 2017) - Bauer, G.; Achleitner, B.; Bonta, M.; Friedbacher, G.; Limbeck, A.
Abstract : Analysis of single particles (∼100 μm) with LA-ICP-MS achieving lateral resolved composition of trace elements via 2D-imaging. Abstract : In environmental questions, particles at the micrometre scale are usually analyzed regarding their particle size and morphology using microscopic techniques. Thereby, their composition and trace element contents are neglected. However, when focusing on recycling and re-use of minor and trace elements in environmental particles like fly ash, originating from municipal waste incineration, information on elemental distribution within single particles may be of grave importance. In this work a procedure for the preparation of fly ash particles for LA-ICP-MS analysis is presented that also allows access to the spatial elemental distribution of each single particle. Herein the particles are dispersed and retained on a sticky substrate, followed by fixation. Roughly one half of the particle is ablated to access the particle cross-section. This cross-section is ablated with consecutive line scans to generate sufficient data to create an image. More than 60 particles with diameters between 25 μm and 100 μm have been analyzed using the presented procedure. General differences in the particle composition could be observed and the elemental distribution of minor constituents like Al, Cu, Pb, Si, Ti and Zn could be visualized for single particles with lateral resolutions down to 2 μm per pixel. Cu and Pb were found to be enriched at the surface, easily accessible for recycling techniques, whereas Ti was found predominantly in the particles' insides. Al, Si and Zn were mostly found to be evenly distributed within particles.